P216 Effect of structured cardiac assessment on survival without readmission after hospitalisation with exacerbation of chronic obstructive pulmonary disease (COPD). (11th November 2022) - Kibbler, JCT; Ripley, DP; Bourke, SC; Steer, J
Abstract : Introduction: In COPD patients heart disease is often underdiagnosed and undertreated. The post-exacerbation period is hazardous, with adverse cardiac events common. A pilot randomised controlled trial of a structured cardiac assessment in patients hospitalised with COPD exacerbation (ECOPD) was undertaken. We report 90-day readmission rates according to whether heart disease was diagnosed and/or treated correctly. Methods: 101 patients hospitalised with ECOPD were randomised 1:1 to receive usual care ± a structured cardiac assessment (SCA) including echocardiogram and CT coronary artery calcium score (CACS). Patients were categorised at the time of hospital discharge: 1) Known Treated heart disease, if any of myocardial infarction, coronary artery disease requiring intervention, left ventricular ejection fraction < 50% or CACS > 100 known and treated according to pre-specified guideline-informed criteria 2) Known Undertreated heart disease, if any of these conditions present but not treated appropriately 3) Known No heart disease, if no diagnosis made by SCA 4) No Known heart disease, if no diagnosis made but SCA not performed. Time to first all-cause readmission or death without readmission, censored at 90 days, was recorded. Results: 100 patients survived to discharge. Mean age 72, median length of stay 5.5 days. Within 90 days, 7/100 patients died. 34/100 experienced readmission. Survival curves separate, showing a trend for patients with Known No heart disease and Known Treated heart disease to be more likely to remain event-free than patients with Known Undertreated heart disease and those whose heart disease status was not intensively investigated. (p=0.119, log-rank test). 27 patients had Known Treated heart disease, with 24 having undergone SCA. 14 (64%) of these achieved Known Treated status via SCA. Conclusions: This pilot study is limited by small numbers but suggests that better diagnosis and appropriate treatment may preserve readmission-free survival at the same level as for patients known to be heart disease-free. A structured cardiac assessment shows promise as an intervention to reduce the burden of death and readmission following hospitalisation with ECOPD. Assessment of the effect of SCA on days alive outside hospital at one year is planned, to inform the design of a definitive randomised controlled trial.